PRINSIP-PRINSIP HUKUM EKONOMI SYARIAH DALAM UNDANG-UNDANG PERBANKAN SYARIAH - Muhamad Kholid (Faculty of Sharia and Law, Sunan Gunung Djati Islamic State University of Bandung, 2018)
AbstractSince Law Number 21 of 2008 concerning Sharia Banking was ratified and promulgated on July 16, 2008, the existence of Islamic Banking in Indonesia has a very strong formal juridical basis so that the institutions, business activities and operations of Islamic banking in Indonesia are required to apply sharia principles. This paper aims to explain the principles of sharia economic law which are adopted and become the foundation of the Islamic banking law. The methodology used in this study is to use analytical descriptive method with a normative juridical approach with qualitative analysis. Based on the results of the discussion, the following research is produced, namely that sharia principles in the Sharia Banking Act can be found in Article 1 paragraph (13), (20), (21), (22), (23), (24), (25), and (28); Explanation of Article 3; Article 5 paragraph (4); Article 19 paragraph (1) letters a, b, c, d, e, f, g, and i; Article 19 paragraph (2) letters a, b, c, d, e, f, g, and i; Article 21; consideration of letter (a); and the phrase